Less than 2% of the Low- and Intermediate-Risk Differentiated Thyroid Cancers Show Distant Metastases at Post-Ablation Whole-Body Scan. Issue 2 (13th April 2019) - Agate, Laura; Bianchi, Francesca; Brozzi, Federica; Santini, Pierina; Molinaro, Eleonora; Bottici, Valeria; Viola, David; Lorusso, Loredana; Vitti, Paolo; Elisei, Rossella
Abstract : Background: Recently, there has been a trend to reduce the use of radioiodine remnant ablation (RRA) in patients with low-risk (LR) and intermediate-risk (IR) differentiated thyroid cancer (DTC). Objectives: The aim of this paper was to evaluate the diagnostic role of whole-body scan (ptWBS) performed after RRA in LR and IR DTC patients. Methods: We analyzed 545 DTC patients treated with total thyroidectomy and RRA in hypothyroidism followed by a ptWBS. Neck ultrasound (US) and serum thyroglobulin measurement were performed. According to the American Thyroid Association guidelines, patients were classified as LR ( n = 345) and IR ( n = 200). Results: In addition to the thyroid remnant, the ptWBS showed the presence of further areas of 131 I uptake in 16/545 (2.9%) cases. ptWBS showed laterocervical lymph node metastases in 11/16 patients (10/11 were also detected by US), mediastinal uptake in 1/16, lung metastases in 3/16, and bone metastases in 1/16. Only 6/545 (1.1%) metastases were detected by ptWBS alone. After 7.8 years, 8/16 patients were free of disease, and 8 had persistent disease: 4 "biochemical" and 4 "structural." Remission was achieved in 3 cases after one single 131 I course, in 1 case after surgery, and in the last 4 cases after several 131 I courses. Conclusions: The ptWBS diagnostic role was clinically relevant for the therapeutic strategies of our patients only in 1.1% of the cases. The cost-effectiveness of performing RRA and ptWBS in all LR and IR patients to find 1–2% of the cases with distant metastases remains controversial.